Effectiveness and safety of vascular intervention plus lenvatinib versus vascular intervention alone for hepatocellular carcinoma patients with portal vein tumor thrombus: a retrospective comparative study - Tang, Saikang; Gao, Yingming; Yan, Xue; Zhi, Weihua; Han, Yue (Frontiers in Oncology, 2024)
Background: This study aimed to assess the effectiveness and safety of vascular intervention combined with lenvatinib versus vascular intervention alone in the treatment of advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT), and to identify prognostic factors associated with the treatment outcomes. Methods: We conducted a retrospective analysis of data from 92 patients with advanced HCC and PVTT who were treated between February 2016 and February 2023. Among them, 56 patients underwent vascular intervention alone (transarterial chemoembolization, TACE), while 36 patients received vascular intervention (TACE or hepatic arterial infusion chemotherapy [HAIC]) combined with combinewithlenvatinib. The primary outcomes, included progression-free survival (PFS), overall survival (OS), and objective response rate (ORR). Survival rates were estimated by the Kaplan-Meier method, and confounders were adjusted using inverse probability of treatment weighting (IPTW). Prognostic factors were determined through the Cox regression model. Results: The median follow-up duration was 20.07 months (interquartile range: 6.41–25.36). The combinationcombined therapy group had a significantly longer median PFS (11.00 vs. 5.00 months, P<0.05) and OS (12.91 vs. 6.83 months, P<0.05) in comparison to the monotherapy group. These findings, and these findings remained consistent after IPTW matching. Moreover, the combinationcombined therapy group showed a higher ORR (55.56% vs. 26.79%, P<0.05) based on mRECISIT criteria. Cox multivariate analysis identified extrahepatic metastasis and maximum tumor diameter as risk factors for PFS, while age, tumor number, and maximum tumor diameter influenced OS. Combined treatment emerged as a protective factor for OS. In the combined combination therapy group, hypertension was the most frequent adverse event (AE), with severe grade 3 or 4 adverse eventsAEs occurring rarely. Conclusion: The combination of vascular intervention with lenvatinib has demonstrated improved PFS and OS in advanced HCC patients with PVTT, and its safety profile appears to be acceptable. Adoption of this combined treatment strategy at an earlier stage may enhance patient outcomes.